Evaluating Community-Based Development in Rural Afghanistan: A Comprehensive Analysis of the National Solidarity Program and Citizens - YAR, Fayaz Gul Mazloum; BAIDAR, Karim Ullah (Community Services: Sustainability Development, 2025)
This study evaluates the effectiveness of community-based development (CBD) initiatives in rural Afghanistan, focusing on the National Solidarity Program (NSP) and the Citizens' Charter National Priority Program (CCNPP). These programs, designed to empower rural communities through participatory decision-making and infrastructure development, have played a critical role in post-conflict reconstruction. Using a mixed-methods approach, this research combines quantitative data from surveys and program reports with qualitative insights from interviews and focus groups to assess the programs' impacts, challenges, and sustainability. Key findings reveal that while the NSP and CCNPP have significantly improved access to basic services and fostered community participation, they face persistent challenges such as fragmented social structures, security constraints, and gender disparities. The study highlights the importance of context-specific approaches, enhanced local governance capacities, and greater gender inclusion to ensure equitable and sustainable outcomes. Additionally, the study addresses the implications of recent political changes, including the Taliban's return to power, on the future of CBD initiatives in Afghanistan. By providing a comprehensive analysis of the NSP and CCNPP, this research contributes to the broader understanding of CBD in conflict-affected settings and offers actionable recommendations for policymakers and development practitioners. The findings underscore the need for adaptive strategies that address Afghanistan's unique socio-political dynamics, ensuring that future CBD programs are more inclusive, resilient, and effective.